STRUCTURAL FEATURES OF RELIGIOUS TERMS IN ENGLISH - Mavlonov Otabek Anvarovich (Western European Studies, 2024)
This article explores the structural features of religious terms in English, focusing on their morphological, phonological, and syntactic characteristics. Through a comprehensive literature review and a detailed analysis of a selected corpus of religious texts, the study identifies key patterns and peculiarities that distinguish religious vocabulary from general English. The findings reveal that religious terms often exhibit unique morphological constructions, specialized phonological patterns, and distinct syntactic usages, reflecting their integral role in conveying complex theological and spiritual concepts.
Keywords: Religious terms; English language; morphology